2022
DOI: 10.1113/jp282531
|View full text |Cite
|
Sign up to set email alerts
|

Local kisspeptin excitation of rat oxytocin neurones in late pregnancy

Abstract: The hormone, oxytocin, is synthesised by magnocellular neurones of the supraoptic and paraventricular nuclei and is released from the posterior pituitary gland into the circulation to trigger uterine contractions during parturition. Kisspeptin fibre density increases around the supraoptic nucleus over pregnancy and intracerebroventricular kisspeptin excites oxytocin neurones only in late pregnancy. However, the mechanism of this excitation is unknown. Here, we found that microdialysis administration of kisspep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Lack of kisspeptin induction of ERK1/2 or p38 phosphorylation in afferent inputs to the oxytocin system While our recent ndings showed that kisspeptin excites oxytocin neurons in late pregnancy, in part, by a direct action of kisspeptin on oxytocin neurons, our ndings also suggested that activation of afferent inputs might also contribute to the excitation (Abbasi et al 2022). Therefore, we mapped kisspeptininduced ERK1/2 and p38 phosphorylation in brain areas that project to the oxytocin system and express Kiss1R and NPFFR (LC, DRN, OVLT, SFO, AVPe, ARC) (Lee et al 1999 Herbison et al 2010).…”
Section: Local Kisspeptin Activation Of Oxytocin Neurons In Late Preg...mentioning
confidence: 43%
See 4 more Smart Citations
“…Lack of kisspeptin induction of ERK1/2 or p38 phosphorylation in afferent inputs to the oxytocin system While our recent ndings showed that kisspeptin excites oxytocin neurons in late pregnancy, in part, by a direct action of kisspeptin on oxytocin neurons, our ndings also suggested that activation of afferent inputs might also contribute to the excitation (Abbasi et al 2022). Therefore, we mapped kisspeptininduced ERK1/2 and p38 phosphorylation in brain areas that project to the oxytocin system and express Kiss1R and NPFFR (LC, DRN, OVLT, SFO, AVPe, ARC) (Lee et al 1999 Herbison et al 2010).…”
Section: Local Kisspeptin Activation Of Oxytocin Neurons In Late Preg...mentioning
confidence: 43%
“…We have recently shown that kisspeptin excites oxytocin neurons in late pregnancy, in part, by a direct action on oxytocin neurons (Abbasi et al 2022). The present study revealed that ICV kisspeptin did not induce ERK1/2 or p38 phosphorylation in oxytocin neurons of non-pregnant or late-pregnant rats when administered at a dose that increases oxytocin neuron ring rate in late-pregnant rats (Seymour et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations